The impacts that interfere with the quality of life of children with epilepsy: An integrative review (Research, Society and Development, 2024)
To look at the scientific evidence on the impacts that interfere with the quality of life of children with epilepsy. Integrative review carried out on the following databases: Latin American and Caribbean Health Sciences Literature (LILACS), Medical Literature Analysis and Retrieval System Online (MEDLINE) and Scientific Electronic Library Online (Scielo). The sample consisted of 10 primary studies, which were conducted between 2008 and 2023 and in Portuguese, Spanish and English. A descriptive method was used to analyze and synthesize the results.When observing the impacts mentioned in the literature, those related to learning stand out, including difficulty learning, memory and lack of attention, social impacts, such as relationships with friends and society, autonomy and the child's behavior; With regard to psychological impacts, those arising with epilepsy or those that begin after discovering the diagnosis due to difficulties and feelings predominate. Family impacts are evident, such as the protection and care that the family has, leading to overload and stress, resulting in a feeling of guilt felt by the child due to the reality experienced by the family. Given the impacts observed, the main ones are those related to school experience, social relationships, psychological and family aspects that are.